Efficacy and safety of Intravaginal Misoprostol versus Intracervical Foley’s catheter for Cervical Ripening - Kharel, Sangita; Lamgade , A; Awale, P (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: The purpose was to compare the efficacy and safety of the intravaginal Misoprostol versus intracervical Foley’s catheter for cervical ripening and labor inductions. Methods: A prospective Randomized controlled trial done among pregnant women requiring induction of labor at the United Mission Hospital, Tansen, Nepal. Primary outcome was proportion of women achieving change in cervical ripening and time required achieving it. Results: One hundred women were randomly assigned to receive intravaginal Misoprostol (n=50) or intracervical Foley’s catheter (n=50). Catheter group showed statistically significant change in Bishop Score than Misoprostol (P <0.037). Oxytocin augmentation (16% vs 58%, P <0.001) and Caesarean delivery (20% vs 28%) were lower in misoprostol group, compared to Foley’s catheter group. Conclusions: Intracervical Foley’s Catheter is a cheap and equally effective method with less complication for cervical ripening as compared with intravaginal Misoprostol